Subjective Tendencies in Ibn Kaṡīr’s Exegesis: A Study of Narrative Selection and Interpretation in QS. al-Baqarah [2]: 21-22 - Anshori, Anshori (Sunan Kalijaga Islamic State University, 2023)
Ibn Kaṡīr’s approach to simplifying and expanding meaning through the citation of various riwayat suggests a subjective tendency in his interpretation. This study aims to uncover Ibn Kaṡīr’s subjective narratives by analyzing his selection and organization of riwāyah, comparing them to the interpretations of earlier scholars who followed similar criteria. The research employs a qualitative methodology, utilizing Julia Kristeva's intertextual analysis model, and focuses on the exegesis of QS. al-Baqarah [2]: 21-22. The study reveals that Ibn Kaṡīr utilized mechanisms of transformation, transposition, and opposition in relation to previous interpretations when explaining these verses. He appears to have distorted the meanings of existing narrations to support his own views, which can be observed in the way he adjusted certain narrations for use in his interpretative process. The variety of narrations provided by earlier scholars is summarized by Ibn Kaṡīr to align with his intended meaning. His selective presentation of certain narrations over others that have equal interpretative potential results in an identity of meaning consistent with his inclination towards Ibn Taymīyah’s interpretative approach. However, unlike Ibn Taymīyah, Ibn Kaṡīr tends to rely on favored narrations to establish a singular meaning. This subjective tendency influences the formation of an interpretative model that emphasizes a subject-object relationship, wherein the Qur'an's own context is overshadowed by the interpreter's will as a subject.